Uji Perbandingan Efektivitas Antibakteri Sabun Cuci Tangan Komersial Berbahan Sirih Hijau, Jeruk Nipis Dan Lidah Buaya Terhadap Bakteri Staphylococcus Aureus - Seran, Dania Ekasanti M.; Pakan, Prisca Deviani; Wungouw, Herman Pieter L; Lidia, Kartini (Cendana Medical Journal, 2022)
ABSTRACTBackground : Currently, there are many antibacterial soap products circulating in the community. To inhibit or kill bacteria, some soaps add an active substance that acts as an antimicrobial. However, repeated use of synthetic soap can cause skin irritation, dry skin, rashes and bacterial resistance. Some soap products add herbal ingredients to reduce side effects, including soap made from green betel, lime and aloe vera.Objective : This study was conducted with the aim of knowing the differences in antibacterial inhibitory ability of hand soap products made from green betel, lime and aloe vera on the market against the growth of staphylococcus aureus bacteria. Methods : The type of research used is a Quasi Eksperimental disc diffusion method with a research design of the Posttest – only Nonequivalent control group design. The treatment group in this study consisted of a positive control (triclosan), a negative control (Sterile distilled water) and commercial handwashing soap made from green betel, lime and aloe vera with 5 repetitions for each group against the staphylococcus aureus bacteria. Data analysis used One Way Anova statistical test with 95% confidence level.Result : Based on the measurement result, the largest inhibition zones were soap made from lime which was 26.4 mm, aloe vera 22.0 mm and green betel 18.8 mm which indicated that each experimental preparation had antibacterial potential and soap made from lime had a more effective inhibitory power in inhibiting the growth of staphylococcus aureus. Analysis of One Way Anova and Dunnet T3 tests obtained p result smaller than a = 0.05, whuch means that there is a significant difference in the mean diameter of the inhibition zone between the treatment groups. Conclusion : There is a significant difference in the antibacterial effectiveness of hand washing soap made from green betel, lime and aloe vera against staphylococcus aureus bacteria.Keywords : Hand soap, Antibacterial, Inhibition, Staphylococcus aureus